Multifocal Necrotizing Sialometaplasia in the Tongue Surgical Specimen: An Immunohistochemical Study - Marques, Marcelo Borges [UNESP]; Posantes, Gabriela Esperanza Maradiaga; Gonçalves, Luana Stefanie Silvino; da Silva, Anderson Tangerino Ferreira; Silveira, Heitor Albergoni; Chahud, Fernando; León, Jorge Esquiche (Springer Nature, 2025)
Background: Necrotizing sialometaplasia (NSM) is a rare self-limiting inflammatory lesion, with most cases affecting the minor salivary glands, especially those located in the palate (70%). To date, about 261 cases of NSM have been reported. Of them, 7 cases affected the tongue; 37 cases occurred after surgery; and 17 cases showed association with neoplasms. Methods: A 50-year-old male patient was diagnosed with squamous cell carcinoma (SCC) of the tongue. After surgical excision, the tumor diagnosis was well-differentiated SCC with a close surgical margin. Re-excision of the margin was indicated. Results: Microscopically, the surgical margin showed neither residual SCC nor epithelial dysplasia. However, it was possible to observe 7 foci containing typical areas of NSM distributed throughout the surgical specimen, which, by immunohistochemistry, revealed a glandular nature with presence of myoepithelial cells. Conclusion: We present here an unusual multifocal NSM affecting the tongue at the site of a prior resection for SCC with close margins, which, to the best of our knowledge, has not been reported to date.
Keywords: Differential diagnosis; Immunohistochemistry; Necrotizing sialometaplasia; Oral cavity; Squamous cell carcinoma